Lake Saloio (Nazare, western Portugal) - Gomes, Sandra (2018)
The Lagoa do Saloio (39◦ 36 48 N, 9◦ 00 57 W) is a small lake situated 5 km east of the town of Nazaré in the Valado de Frades forest, central coast of Portugal. The lake is 70 m above sea level, 270 m long, 72 m wide, and oriented west-southwest–eastsoutheast (WSW–ESE). The site is a groundwaterfed, interdunal lake (Queiroz & Mateus, 2004) located on the border between Plio-Pleistocene sands of the Valado de Frades complex and more recent dunefields (Camarate França & Zbyszewski, 1963). The local soils are mostly podsols and regisols with fertile alluvial soils distributed along the Alcoa River.